Dementia and Depresion: A Glance of Neuropsychiatry - Devi Ramadianti (Scientia Psychiatrica, 2021)
Dementia has a complex disease course and one of them can affect the psychology of the sufferer. People with dementia tend to experience stress and anxiety symptoms due to the limitations they experience. This article will provide a theoretical overview of the relationship between the two in general and theoretically so that it can be understood that the two are a unity in the neuropsychiatric aspect.